Endotracheal intubation training to medical practitioners: Comparison of the modified 4-step Payton's training method and Halsted's training method in a simulated environment - Majid Zamani; Mohammad Nasr-Esfahani; Mostafa Forghani; Mohammadreza Asadollahian Sichani; Athar Omid (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The ability of physicians to perform endotracheal intubation by laryngoscope is one of the essential skills. The purpose of this study was to evaluate the effectiveness of the four-step python training method with the Halsted's "See one, Do one, and Teach one" training method in endotracheal intubation competency in simulated environment. MATERIALS AND METHODS: This quasi-experimental study was performed on two independent groups with posttest. The statistical society consisted of eighth-semester medical students referred to the emergency medicine unit. The experimental group received a modified four-step python's training method that modified for small groups, and the control group received the Halsted's "See one, Do one, and Teach one" training method. Researcher-made checklist used to rate participant competency as posttest. Data were analyzed using SPSS 19 software. RESULTS: Sixty-seven students volunteered for the experimental group and 57 students for the control group. In posttest, the experimental group more competent than the control group significantly (P < 0.001). Furthermore, the training course satisfaction of the experimental group was significantly higher than the control group (P < 0.001). DISCUSSION AND CONCLUSION: Modified python training method for small groups has shown a better effect on student performance. This finding is consistent with previous researches. Modified four-step python's training for small group with an emphasis on peer to peer teaching and receiving feedback from peer can be related to the effectiveness of this training. Further research is recommended in other clinical education settings.